Euthanasia as a professional dilemma in nursing students - María Verónica Aveiga Hidalgo; Clara Eliza Pozo Hernández; Olga Mireya Alonso Pico; Erika Marcela León Ravelo (Medisur)
Foundation: the World Health Organization defines euthanasia as the deliberate action carried out by a person with the intention of causing the painless death of another subject, or not preventing death from natural causes, in case of terminal illness or irreversible coma. Objective: to identify the information level about euthanasia as a professional dilemma in sixth level nursing students. Methods: descriptive, cross-sectional research carried out from October 2021 to March 2022 at the Los Andes Regional Autonomous University. The studied population was 43 sixth level nursing students. The studied variables were: perception of the euthanasia definition, personal criteria on the application of euthanasia, perception of the doctor’s determination in the use of euthanasia and criteria of the students on the indicated person to decide on euthanasia. Results: 79 % recognize that euthanasia is a procedure that helps end the life of the patient who is critically ill. 46% believe that euthanasia should only be applied to patients with incurable diseases. Almost half of those surveyed believe that the doctor should determine the application of euthanasia. More than half responded that the person indicated to decide on euthanasia should be the patient himself. Conclusions: the euthanasia conflict is determined by the ethics involved in the matter in question.